Brain plasticity in Diptera and Hymenoptera - Groh, Claudia (2010)
To mediate different types of behaviour, nervous systems must coordinate the proper operation of their neural circuits as well as short- and long-term alterations that occur within those circuits. The latter ultimately devolve upon specific changes in neuronal structures, membrane properties and synaptic connections that are all examples of plasticity. This reorganization of the adult nervous system is shaped by internal and external influences both during development and adult maturation. In adults, behavioural experience is a major driving force of neuronal plasticity studied particularly in sensory systems. The range of adaptation depends on features that are important to a particular species, so that learning is essential for foraging in honeybees, while regenerative capacities are important in hemimetabolous insects with long appendages. Experience is usually effective during a critical period in early adult life, when neural function becomes tuned to future conditions in an insect's life. Changes occur at all levels, in synaptic circuits, neuropile volumes, and behaviour. There are many examples, and this review incorporates only a select few, mainly those from Diptera and Hymenoptera.